Automatic Removal of Low Frequency Noise from Seismograms Using the Fingerprinting Method: Algorithms, Properties, Limitations - Silkin, K. Yu (Journal of volcanology and seismology, 2024)
This paper describes a new method for automatic preparation of a noisy seismic record for further analysis using expert information systems. The method is based on seismogram fingerprints, which, due to their concise but informative pattern, allow the development of a reliable algorithm for finding important noise characteristics. The search for the optimal cutoff frequency for a high-pass filter is especially important under conditions of partial overlap of the signal and noise spectra, when the latter have high intensity. It is precisely this difficult case that this study aims to address. The article analyzes the methodology developed here in application to several hundred records of regional earthquakes and explosions. The analysis showed that reliable results can be achieved in more than 90% of the cases. In addition, the defects and limitations of the method are mentioned, which are logical consequences of its advantages. The Appendix to this article contains a detailed description of the algorithm underlying the method.